PENYELENGGARAAN SISTEM ELEKTRONIK DI DKI JAKARTA BERDASARKAN PERATURAN MENTERI KOMUNIKASI DAN INFORMATIKA NOMOR 5 TAHUN 2020 TENTANG PENYELENGGARASISTEM ELEKTRONIK LINGKUP PRIVAT - Ahmad Raditya Yunizar; Gusliana HB; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Minister of Communication and Informatics issued regulations regarding private electronicsystem operators through Ministerial Regulation Number 5 of 2020 concerning Private ElectronicSystem Operators. In the ratification of these regulations, according to the requirements for theimplementation of state administrative law, one of the conditions was violated, namely legitimacy, whichmeans that state administrative activities should not cause commotion because they are not acceptableto the local community or the environment concerned.The enactment of this regulation creates problems in the community and disrupts communityactivities, starting from the economic and social aspects. In the implementation of the ministerialregulation there are still many obstacles to achieving the objectives of the regulation. The ministerialregulation also contradicts the regulations above it, namely the Electronic Information and TransactionLaw. By going through an empirical approach with the aim of answering issues based on the scientificside as well as field factsThe results of this research are that the government in enforcing regulations still has somedeficiencies starting from socialization, deficiencies in human resources who master technology, andthere are still many companies that ignore these regulations which impact on the wider community. Forthis reason, it is necessary to disseminate information related to these regulations to the widercommunity and to strengthen human resources who understand technology so that problems do notoccur in the future so that in the future these regulations can improve the quality of the state in any field.Keywords: Implementation, Regulation of the Minister of Communication and Informatics, PrivateElectronic System Operators.